Optimalisasi Proses Verifikasi Chart Prosedur di Pelayanan Informasi Aeronautika Wilayah - Kinanti Rindang Utami; Togi Adnan Maruli Sinaga; Emilia Rahajeng Larasati (LPPM Politeknik Pratama, 2025)
The verification process of procedure charts within the Aeronautical Information Services (AIS) plays a crucial role in ensuring the quality of navigation data published in the Aeronautical Information Publication (AIP). This study aims to examine the verification mechanism of procedure charts conducted by Aeronautical Information Services (PIA) Regional Units, considering the significant amount of user feedback regarding data inconsistencies. A qualitative approach was employed through observation, document analysis, and semi-structured interviews with three PIA Regional Units and the Cartography Unit at PIA Headquarters. The findings reveal discrepancies between verification practices and applicable regulations, as PIA Regional Units did not verify draft procedure charts submitted by the procedure design unit. The study recommends enhancing personnel understanding of Standard Operating Procedures (SOP), reinforcing accountability, establishing specific technical parameters for chart verification at the regional level, and providing personnel training.